Not a minute more : ending violence against women - Jacobs, Gloria (UNIFEM, 2003)
This report surveys gender-based violence from various nations around the world. Expert consultants conducted regional analyses of violence against women and produced this unique publication that provides an in-depth picture of the various forms of violence experienced by women. It highlights, country by country, many of the recent achievements and indicates what must continue to build on them. Additionally, it provides examples of good practices as well as efforts that did not meet the goals and explores the reasons why. Lastly, it provides tools, case studies and inspiration that will allow readers to understand the challenges that lie ahead and what the most fruitful next steps might be.